Water availability drives gradients of tree diversity, structure and functional traits in the Atlantic–Cerrado–Caatinga transition, Brazil. (4th June 2018) - Terra, Marcela de Castro Nunes Santos; Santos, Rubens Manoel dos; Prado Júnior, Jamir Afonso do; de Mello, José Marcio; Scolforo, José Roberto Soares; Fontes, Marco Aurélio Leite; Schiavini, Ivan; dos Reis, Aliny Aparecida; Bueno, Inacio Thomaz; Magnago, Luiz Fernando Silva; ter Steege, Hans
Abstract: Aims: Climate and soil are among the most important factors determining variation in tree communities, but their effects have not been thoroughly elucidated to date for many vegetation features. In this study, we evaluate how climate and soil gradients affect gradients of vegetation composition, species diversity and dominance, structure and functional traits (seed mass and wood density) using over 327 000 trees in 158 sites distributed along environmental gradients in the transitions among the Atlantic forest, Cerrado and Caatinga in Minas Gerais State (MG), Brazil (nearly 600 000 km 2 ). Methods: Gradients in species, genus and family abundance in addition to basal area, stem density, species diversity (Fisher's alpha), dominance percentage, seed mass and wood density were correlated using multiple regressions with environmental variables, as summarized in four principal component analysis axes (two climatic—precipitation seasonality and temperature range—and two edaphic—soil fertility and soil moisture). Additionally, ordinary kriging maps were used to better illustrate the gradients. Important Findings: Multiple regression models indicate that all variables but dominance percentage were affected by one or more of the environmental gradients, but the average R 2 was low (26.25%). Kriging maps reinforced the patterns observed in the regression models. Precipitation seasonality and soil moisture gradients were the most important gradients affecting vegetation features. This finding suggests that water availability is an important determinant of vegetation features in these vegetation transitions.